Islamic Law Principles in Islamic Business Activity - Prawitra Thalib, - (Primrose Hall Publishing Group, United Kingdom, 2020)
Islam provides solutions to all kinds of complicated problems, which are faced by human beings such as materialism, nationalism, race, ethnicity, and religion. Islam has its own way to solve these problems, especially in case of economy and business activity. This paper aims to discuss the application of Islamic law principles towards economic and business activity. This paper uses descriptive research methodology by gathering data from books and the Quran. Islamic Business includes norms or values within Islamic law that prohibit usury, dishonest trade, unjust treatment, and all forms of oppression and discrimination. Islam provides guidance for economic and business activity. Thus, Islamic business activity has to apply the basic principles of Islamic law in order not to break Islamic law.